Targeting cholecystokinin‐2 receptor for pancreatic cancer chemoprevention. Issue 10 (16th July 2019) - Mohammed, Altaf; Janakiram, Naveena B; Suen, Chen; Stratton, Nicole; Lightfoot, Stanley; Singh, Anil; Pathuri, Gopal; Ritchie, Rebekah; Madka, Venkateshwar; Rao, Chinthalapally V
Abstract: Gastrin signaling mediated through cholecystokinin‐2 receptor (CCK2R) and its downstream molecules is altered in pancreatic cancer. CCK2R antagonists, YF476 (netazepide) and JNJ‐26070109, were tested systematically for their effect on pancreatic intraepithelial neoplasia (PanIN) progression to pancreatic ductal adenocarcinoma (PDAC) in Kras G12D mice. After dose selection using wild‐type mice, six‐week‐old p48 Cre/+ ‐LSL‐Kras G12D (22‐24 per group) genetically engineered mice (GEM) were fed AIN‐76A diets containing 0, 250, or 500 ppm JNJ‐26070109 or YF‐476 for 38 weeks. At termination, pancreata were collected, weighed, and evaluated for PanINs and PDAC. Results demonstrated that control‐diet‐fed mice showed 69% (males) and 33% (females) incidence of PDAC. Administration of low and high dose JNJ‐26070109 inhibited the incidence of PDAC by 88% and 71% ( P  < .004) in male mice and by 100% and 24% ( P  > .05) in female mice, respectively. Low and high dose YF476 inhibited the incidence of PDAC by 74% ( P  < .02) and 69% ( P  < .02) in male mice and by 45% and 33% ( P  > .05) in female mice, respectively. Further, transcriptome analysis showed downregulation of Cldn1, Sstr1, Apod, Gkn1, Siglech, Cyp2c44, Bnc1, Fmo2, 623169, Kcne4, Slc27a6, Cma1, Rho GTPase activating protein 18, and Gpr85 genes in JNJ‐26070109‐treated mice compared with untreated mice. YF476‐treated mouse pancreas showed downregulation of Riks, Zpbp, Ntf3, Lrrn4, Aass, Skint3, Kcnb1, Dgkb, Ddx60, and Aspn gene expressions compared with untreated mouse pancreas. Overall, JNJ‐26070109 showed better chemopreventive efficacy than YF476. However, caution is recommended when selecting doses, as the agents appeared to exhibit gender‐specific effects.